The potential of artificial intelligence in early diagnosis and personalized treatment: Advances and challenges in modern medicine (Research, Society and Development, 2024)
Carrying out this study is justified by its academic, scientific and social relevance, based on presenting technological advances involving artificial intelligence in healthcare. Therefore, the objective of this research focuses on highlighting the applications and benefits of Artificial Intelligence in Medicine. This study was carried out through an integrative literature review, with an exploratory approach, whose institute was limited to investigating, through already published articles, relevant information that answered the guiding question. Thus, data collection took place in scientific bases: SCIELO and LILACS. One of the main advantages of using AI in early diagnosis is the ability to process large volumes of data quickly and accurately, identifying patterns and signals that may be imperceptible to human healthcare professionals. This makes it possible to detect serious medical conditions early, such as cancer and heart disease, when treatment is most effective and the chances of recovery are greatest. Furthermore, AI can significantly contribute to personalized treatment, adapting therapeutic approaches based on the individual characteristics of each patient. By analyzing genetic data, medical history, and response to previous treatments, AI algorithms can help doctors develop treatment plans that are more effective and have fewer side effects.